2009
DOI: 10.1002/jsfa.3838
|View full text |Cite
|
Sign up to set email alerts
|

Experimental evidence for the protective effects of coffee against liver fibrosis in SD rats

Abstract: Coffee exerts protective effects against liver fibrosis via antioxidant action and the suppression of fibrogenic cytokines, TGF-beta and PDGF-beta.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
25
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 31 publications
7
25
0
1
Order By: Relevance
“…This comes into agreement with the results of previous investigators who reported the heptoprotective effect of coffee and caffeine against liver injury induced by thioacetamide in male Wistar rats [23]. In addition, the antifibrotic action of caffeine was evaluated in our study by reducing the hepatic content of hydroxyproline which is an indicator for the deposition of collagen and this result are in harmony with that of previous investigators who reported an experimental evidence for the protective effects of coffee against liver fibrosis in sprague dawley (SD) male rats [24].…”
Section: Discussionsupporting
confidence: 90%
“…This comes into agreement with the results of previous investigators who reported the heptoprotective effect of coffee and caffeine against liver injury induced by thioacetamide in male Wistar rats [23]. In addition, the antifibrotic action of caffeine was evaluated in our study by reducing the hepatic content of hydroxyproline which is an indicator for the deposition of collagen and this result are in harmony with that of previous investigators who reported an experimental evidence for the protective effects of coffee against liver fibrosis in sprague dawley (SD) male rats [24].…”
Section: Discussionsupporting
confidence: 90%
“…Shin et al . used immunohistochemical staining to demonstrate that caffeine‐containing beverages can decrease α‐SMA expression . To assess the antifibrotic effects of caffeine, we measured the expression of procollagen type Ic and α‐SMA in liver tissue in vitro and in vivo .…”
Section: Discussionmentioning
confidence: 99%
“…In the hepatic parenchyma, the protective effects of coffee are characterized by alleviating the oxidative stress and inflammation reduction (Lv et al 2010). Other studies have also reported the effect of caffeine on weight reduction (Shin et al 2010) due to increased thermogenesis, increasing the rate of lipolysis and fat oxidation (Greenberg et al 2006) and speed up the metabolism energy and reduce lipogenesis (Murase et al 2011). However, caffeine also has some adverse effects involving the cardiovascular system (Papamichael et al 2005), association with the occurrence of spontaneous abortion and stillbirth (Bech et al 2005) and withdrawal effects, such as sleep problems and fatigue (Phillips-Bute and Lane 1997).…”
Section: Introductionmentioning
confidence: 99%